GOVERNANCE MATTERS: INSIGHTS INTO EUROPEAN UNION FUND ABSORPTION ACROSS SUCCESSIVE MULTIANNUAL FINANCIAL FRAMEWORKS - Diana BĂLAN; Ana-Cristina NICOLESCU (Annals of the University of Oradea: Economic Science)
This paper explores the relationship between governance quality and European Structural and Investment Funds (ESI Funds) efficiency at the European Union (EU) level. This research proposes a new approach by classifying Member States into distinct groups based on governance indicators and ESI Funds absorption. The study uses a comprehensive dataset for 27 EU Member States from 2007 to 2022. This time frame covers the last two multiannual financial frameworks (MFFs): 2007-2013 and 2014-2020. The main results reveal a clear connection between the quality of governance and the degree of ESI Funds absorption for each period. Countries with high regulatory standards, the rule of law, and government efficiency demonstrate remarkable results in absorbing ESI Funds. These findings highlight the essential role of aligning national regulations with those of the EU. On the other hand, low levels of these governance indicators generate deficiencies in managing these financial resources. The comparative analysis of the two MFFs reveals notable progress in streamlining European funds' regulations and absorption process. The reduction in the number of clusters from six in 2007-2013 to four in 2014-2020 signifies a more streamlined and efficient distribution and absorption of ESI Funds. Countries with robust governance systems, such as Denmark, Finland, and Sweden, demonstrate tangible advantages in managing these funds. On the other hand, countries with weaker governance, including Romania and Bulgaria, demonstrate a low absorption rate. Intermediate clusters with a moderate level of all indicators – such as Italy and Spain – oscillate between the groups in which they are located, which reveals both periods of progress and stagnation. The insights gained from this research underline the importance of fostering governance reforms tailored to the specific needs of Member States to ensure fair and balanced utilisation of European financial resources. This study provides valuable information for policymakers, highlighting the need to adapt monitoring mechanisms to identify the individual challenges and opportunities of each Member State. The analysis promotes equitable development in the European Community by strengthening administrative capacities and reducing inequalities.